2017
DOI: 10.1149/2.0271711jss
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 2 MeV Proton Irradiation on the Large-Signal Performance of Ka-Band GaN HEMTs

Abstract: GaN high electron mobility transistors (HEMTs) have shown the potential to be extremely tolerant of the space radiation environment. To understand whether this radiation tolerance extends to millimeter wave GaN technology nodes, we have investigated the performance of discrete devices made with a commercial Ka-band AlGaN/GaN HEMT process after exposure to 2 MeV proton irradiation. In addition, we evaluate the large signal RF performance to enable the extraction of relevant device metrics (output power, gain, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The shift from GaAs to GaN led to an approximate improvement of 1000% improvement in radiation resistance. [3][4][5][6][7][8][9] While the bond energy of Ga-As is only 2.17 eV, the bond strength of Ga-N is 9.12 eV. This 4 fold increase in bond strength is not proportionally reflected in the performance improvement, the remainder is likely due to the piezoelectric field at the channel barrier layer interface of AlGaN/GaN reinjecting scattered carriers into the 2DEG.…”
mentioning
confidence: 99%
“…The shift from GaAs to GaN led to an approximate improvement of 1000% improvement in radiation resistance. [3][4][5][6][7][8][9] While the bond energy of Ga-As is only 2.17 eV, the bond strength of Ga-N is 9.12 eV. This 4 fold increase in bond strength is not proportionally reflected in the performance improvement, the remainder is likely due to the piezoelectric field at the channel barrier layer interface of AlGaN/GaN reinjecting scattered carriers into the 2DEG.…”
mentioning
confidence: 99%
“…Alpha particle radiation due to its heavier mass presents a larger risk to both electronics and life forms in space than proton irradiation. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Alpha particle events in GaN High Electron Mobility Transistors (HEMTs) have been studied previously, although not nearly as well as proton irradiation. Danesin et al reported on 2 MeV alpha irradiation and noted a 70% reduction on drain current at a fluence of 10 14 cm −2 .…”
mentioning
confidence: 99%
“…AlGaN/GaN high electron mobility transistors (HEMTs) along with SiC transistors and diodes have become the backbone of power management and RF applications for extraterrestrial applications due to their wide bandgap, high critical electric field, low switching loss, and intrinsic radiation hardness. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Another key application is the insertion of these types of devices into instrumentation for nuclear fission and fusion reactors. The still-under-construction International Thermonuclear Experimental Reactor (ITER) is expected to produce neutron radiation with energies in the range of 2-14 MeV and fluences of up to 10 14 cm −2 per second.…”
mentioning
confidence: 99%